PRESERVASI ARSIP KONVENSIONAL DI ARSIP UNIVERSITAS GADJAH MADA - , HANIF AULIA RAHMAN; , Dra. Eny Kusumindarti W ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Preservation is part of the life cycle of records. Preservation activities are controlling, maintenance, care, prevention, and repair the archives of damaging elements. This final assignment is to discuss the methods of preservation conventional archive with a focus research on textual and cartographic archive in the Gadjah Mada University Archives. Data collection methods using interviews, observations, participate in the process of preservation of archives, and gather additional theories from library collection. In this final assignment will be discussed the basic concepts of preservation, a preservation methods that used by Gadjah Mada University Archives, application of environmental controls on archival management, and constraints encountered. The conclusion of this final assignment, Gadjah Mada University Archives has doing a conventional archive preservation structured in accordance with the basic provisions of the preservation system. Constraints faced by the limitations of the equipment and only as the place of processing.